Addressing the exciton fine structure in colloidal nanocrystals: the case of CdSe nanoplatelets. Issue 2 (14th December 2017) - Shornikova, Elena V.; Biadala, Louis; Yakovlev, Dmitri R.; Sapega, Victor F.; Kusrayev, Yuri G.; Mitioglu, Anatolie A.; Ballottin, Mariana V.; Christianen, Peter C. M.; Belykh, Vasilii V.; Kochiev, Mikhail V.; Sibeldin, Nikolai N.; Golovatenko, Aleksandr A.; et al.
Abstract : Exciton fine structure in colloidal CdSe nanoplatelets. Abstract : We study the band-edge exciton fine structure and in particular its bright-dark splitting in colloidal semiconductor nanocrystals by four different optical methods based on fluorescence line narrowing and time-resolved measurements at various temperatures down to 2 K. We demonstrate that all these methods provide consistent splitting values and discuss their advances and limitations. Colloidal CdSe nanoplatelets with thicknesses of 3, 4 and 5 monolayers are chosen for experimental demonstrations. The bright-dark splitting of excitons varies from 3.2 to 6.0 meV and is inversely proportional to the nanoplatelet thickness. Good agreement between experimental and theoretically calculated size dependence of the bright-dark exciton splitting is achieved. The recombination rates of the bright and dark excitons and the bright to dark relaxation rate are measured by time-resolved techniques.